(3GdJQhjL hGdGYdGfs - (3SejQ YHO GdQRGb(B, (3GdYHOdjs; (3GdYHOdj(B, (3bMWGf HOQs ((3YeGf(B:s (3OGQ RgQGf ddfTQ hGdJhRjY(B,s, 2006)
(3GdJQhjL hYfGUQg,fTCI hJWhQ GdGYdGf,hXGFa hCgOGa GdEYdGf,EOGQI GdEYdGf,hcGdGJ GdEYdGf,GdhSGFd GdGYdGfjI,GdJNWjW ddMedGJ GdGYdGfjI,ejRGfjI GdGYdGf,GdYhGed GdeDKQI Ydi aGYdjI GdEYdGf,JUeje GdEYdGf hGNQGLg,GdCgejI GdGbJUGOjI hGdGLJeGYjI ddEYdGf,GdGYdGf hGdSdhc GdGSJgdGcj,GdHjY GdTNUj,JQhjL GdeHjYGJ,GdOYGjI hGdYdGbGJ GdYGeIs
(3HHdjhZQGajG(B:(3U(B.442 -243s
Keywords: (3GdGYdGfs; (3GdJShjbs